2014
DOI: 10.12748/uujms.201416504
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metakaolin and end type of steel fiber on fiber-SIFCON matrix bond characteristics

Abstract: SIFCON (Slurry Infiltrated Fiber Concrete) can be described as a special type of cement based composite produced with fiber volume fraction values between 5 to 30%. As a result of superior mechanical properties such as compressive, tensile, shear and flexural strengths with extraordinary toughness values, SIFCON can be used in in industrial floors, repair and reinforcement works and military applications such as anti-missile hangers. Mechanical properties of fiber reinforced cement based composites are dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
1
0
1
Order By: Relevance
“…Similarly, Lee et al (2012) [179] reported that the addition of metakaolin and silica fume efficiently improves the polyvinyl alcohol fiber-cement mortar bond strength by an optimum dosage of 10% for metakaolin. The literature confirmed these promising results for metakaolin and nano-clay with specific dosages [180,181].…”
Section: Bond Strengthsupporting
confidence: 57%
“…Similarly, Lee et al (2012) [179] reported that the addition of metakaolin and silica fume efficiently improves the polyvinyl alcohol fiber-cement mortar bond strength by an optimum dosage of 10% for metakaolin. The literature confirmed these promising results for metakaolin and nano-clay with specific dosages [180,181].…”
Section: Bond Strengthsupporting
confidence: 57%
“…In limited studies, the effect of silica fume, metakaolin, slag and fly ash on the bond behaviour of fibres in cement matrix are evaluated. Yalcinkaya et al [9] reported about 12% and 10% increase in pull-out load of hook end steel fibre in cement matrix due to partial replacement of cement with 15% and 30% metakaolin, respectively. In the case of straight steel fibre this improvement was below 5% in both metakaolin contents.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to systematically investigate the effects of UV radiation on the carbonation behaviour of cement-based materials and clarify the related mechanism and thus establish a theoretical and experimental basis for engineering cement-based materials. Three SCMs, namely silica fume (SF), blast furnace slag (GGBS), and metakaolin (MK), were selected to partially replace cement in the preparation of cement pastes, which were subsequently subjected to UV and standard (non-UV) curing after hardening [19][20][21][22][23]. The pH of the paste at different depths from the exposed surface was evaluated for each layer to characterise the effect of the UV radiation depth.…”
Section: Introductionmentioning
confidence: 99%